Comparative Trial of Continuous Flow Enteral and Intravenous Fluid Therapy in Horses - Dias, Domingos C. R.; Ribeiro Filho, José D.; Viana, Rinaldo B.; Bittencourt, Thereza C. C.; Dantas, Fernanda T. D. R.; Teixeira, Raffaella B. C.; Di Filippo, Paula A.; Manso Filho, Hélio C.; Alves, Samuel R.; Santos, Paulo V. M.; Moreira, Nadyne S. (Frontiers in Veterinary Science, 2021)
Enteral fluid therapy in continuous flow with isotonic and hypotonic enteral electrolyte solutions are as safe and effective as intravenous fluid therapy. The aim of this study was to carry out a comparative assessment between continuous flow enteral and intravenous fluid therapy in adult horses experimentally dehydrated. Six experimentally dehydrated adult mares were used in a study carried out in a 6x3 crossover design, which each animal received three different treatments (isotonic enteral fluid therapy – EsISO, hypotonic enteral fluid therapy – EsHYPO and intravenous fluid therapy with Lactate Ringer Solution – LR IV, all in continuous flow). Solutions were administered at a rate of 15 mL-1.kg-1.h-1 for 8 hours, after 36 hours of water and food deprivation. Serum and urinary biochemical assessment; urinary volume, pH and specific gravity; and blood gas analysis were measured at -36h, 0h, 2h, 4h, 6h and 8h. The dehydration period (DP) caused discrete hydroelectrolytic and acid base imbalances. The EsISO, EsHYPO and LR IV treatments restored the imbalances yielded by the DP in addition to increasing urine volume. The present study certifies the efficacy and safety of isotonic and hypotonic enteral fluid therapy in continuous flow in comparison to intravenous fluid therapy to replace blood volume in dehydrated horses.